La internacionalización de las universidades como instrumento de diplomacia pública de los estados. Internationalization of universities as States public diplomacy instrument - García Waldman, David Horacio; Lugo Rincón, Paulo César (Red Iberoamericana de Academias de Investigación, 2019)
A consequence of globalization process, States seen the need in the application of many instruments to get a major benefit of said process. Therefore the present article has as purpose the analysis of the internationalization of the universities as a possible instrument in the application the application of what is conceptually known public diplomacy. For the realization of this study It has been made an exhaustive literature review about the public diplomacy and the internationalization of the universities.